5G User Equipment Phased Array Antenna Architecture for Millimeter Wave Beamforming Applications - ElGhanam, Eiman Ayman Mahmoud (2018)
A Master of Science thesis in Electrical Engineering by Eiman Ayman Mahmoud ElGhanam entitled, “5G User Equipment Phased Array Antenna Architecture for Millimeter Wave Beamforming Applications”, submitted in December 2018. Thesis advisor is Dr. Lutfi Albasha and thesis co-advisors are Dr. Nasser Qaddoumi and Dr. Hassan Mir. Soft and hard copy available.